Pemodelan Banjir di Wilayah Pedesaan Kabupaten Cirebon dengan Menggunakan HEC-RAS dan ArcGIS - Farhan, Ohan; Hariani, Mira Lestira; Priyono, Cecep (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Flood modeling is crucial as part of disaster mitigation efforts in a region. This study aims to determine the extent and depth of flood inundation using ArcGIS 10.8 and analyze flood modeling using HEC-RAS 6.3.1 to predict potential flooding in rural areas of Cirebon District. Rainfall analysis was conducted using the Thiessen Polygon method based on ten years of maximum rainfall data, while flood analysis was carried out using the Nakayasu Synthetic Unit Hydrograph (HSS) method. The study results indicate that rice fields were the most affected area, covering approximately 45.95 hectares with an inundation depth ranging from 1 to 2 meters. To mitigate flood impacts, an increase in embankment height by 1.5 meters is recommended at several critical points. Keywords : Flood mitigation, Flood Modelling, HEC-RAS, ArcGIS, HSS Nakayasu